Survey of Software Maintenance Metrics: A Systematic Literature Review - Machado, Jackson; Kemczinski, Avanilde; Schroeder, Rebeca (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2023: Anais do XIX Simpósio Brasileiro de Sistemas de Informação, 2023)
The software maintenance area is one of the oldest in software engineering, which is a fundamental role in all development, ensuring the final product quality and stability in the market. However, the control of software maintenance metrics becomes a difficult task, as there are no consistent applicability normalization for these metrics, and it is up to the software maintenance teams to decide which metrics to apply. In order to identify the main metrics used in the software maintenance area, we carried out a systematic review of the literature on the relevant studies published in the period between 1990-2020 into the main search engines in the area of software engineering. According to the keywords and inclusion and exclusion criteria, 44 out of 2145 articles were selected on the IEEE, ACM Digital Library, ScienceDirect, SCOPUS and Wiley Interscience. Thus, the software maintenance metrics were identified in the product, process and resource perspectives more widely directed towards the product, as well as the application validation of these metrics are made through technical experimentation of the measurement, that is, validations in a controlled environment that often do not match the reality of the software maintenance environment. Therefore, it is highlighted that the analysis of software maintenance metrics is a promising area for new researches targeting distinct perspectives, including in a real software maintenance environment.